Pengaruh Kepuasan Kerja, Stres Kerja, dan Komitmen Organisasional terhadap Turnover Intention - Dina Sabta Ratnaningsih (Jurnal Ilmu Manajemen, 2021)
This study aims to find the results of analyzing the phenomena encountered in Elresas Hotel employees regarding job satisfaction, job stress, and organizational commitment as independent variables on turnover intention as the dependent variable on Elresas Hotel employees. The research is quantitative, with variables measured using a Likert scale. Data collection use questionnaires and direct observation. This study uses the entire population of Hotel Elresas Lamongan, amounting to 40 people, as a sample. The data obtained were processed using SPSS Vs 18 software in descriptive analysis, classical assumption test and data analysis using multiple linear regression analysis. To test the significance level, simultaneous F-test and t-test were carried out. The research conducted concluded that job satisfaction had a partially insignificant effect on turnover intention, job stress had a positive and significant effect on turnover intention, and organizational commitment partially had an insignificant effect on turnover intention. Simultaneously both the variables of job satisfaction, job stress and organizational commitment influence turnover intention. This study is intended to find out the factors that cause turnover intention at Hotel Elresas Lamongan and can also be used as a suggestion so that employees do not have thoughts of leaving their jobs.